Penerapan Asas Sederhana, Cepat, Dan Biaya Ringan Dalam Pelaksanaan Modernisasi Persidangan Perkara Pidana Berdasarkan Cetak Biru Pembaharuan Peradilan Tahun 2010-2035 Pada Pengadilan Negeri - Purwo Widodo; Yusrianto Kadir; Arifin Tumuhulawa (Jurnal Hukum Bisnis, 2024)
This study aims to analyze the application of simple, fast and low-cost principles to judicial institutions in criminal trial processes. The research method used is normatic-empirical research, namely Library Research which is complemented by Field Research (empirical) by collecting direct information through interviews with parties related to the statutory approach (statute approach), conceptual approach (conceptual aapproach). The results show that Modernization of Justice in the trial of Criminal Cases is a demand of changes in world society in the era of globalization. Modernization of Criminal Justice has been accelerated by global challenges by utilizing IT with the holding of Electronic Criminal Trials with the aim of providing legal certainty to Defendants, where electronic trial is held as a form of application of the principles of fast, simple and light costs that have been stipulated in the Criminal Procedure Code in the implementation of criminal trials themselves.